GENDER ROLES IN MODERN DYSTOPIAN NARRATIVES: A FEMINIST PERSPECTIVE - Hemavathi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Modern dystopian literature and media often serve as a mirror reflecting societal anxieties and inequalities. However, within these narratives, the portrayal of gender roles remains an area of concern. While dystopian settings offer opportunities to critique societal norms, they often reinforce traditional gender stereotypes. This paper analyzes gender roles in modern dystopian narratives through a feminist lens, highlighting the complexities of female representation and their evolving roles in these speculative worlds. By examining key texts and media, the study underscores the importance of inclusive narratives that challenge established gender norms and reflect diverse identities.